Sea urchin Arbacia punctulata feeding preference for algal turf over kelp in a degraded kelp forest ecosystem - Kelly, Sophia R.; Hamel, Kenneth; Narvaez, Carla A.; Armstrong, Thomas J.; Grace, Sean P.; Feehan, Colette J. (Journal of Experimental Marine Biology and Ecology, 2024)
Climate change is driving a shift in the distribution of global kelp forests, with the contraction of kelp habitats occurring at warm range edges. Declining kelps often have been replaced by novel algal turf assemblages, which are reinforced by ecological feedback mechanisms and provide fewer ecosystem services. Trophic interactions among marine herbivores, algal turfs, and kelps on algal turf-dominated reefs remain poorly resolved but could have important implications for the stability of algal turf reefs and the potential for kelp forest recovery. Here, we examine herbivory by the Atlantic purple sea urchin, Arbacia punctulata, in a degraded kelp forest ecosystem dominated by algal turf in southern New England, USA. In a localized field survey, we observed lower algal turf cover on reef areas containing A. punctulata (mean ± SE: 62 ± 12% turf cover) as compared to areas with no sea urchins present (92 ± 4% turf cover). Reef areas with and without sea urchins had similarly low cover of the previously dominant kelp, Saccharina latissima (6–8% kelp cover). In laboratory and field experiments, individuals or groups of A. punctulata enclosed with a diet choice of algal turf versus kelp had higher grazing rates on the algal turf. A. punctulata in the laboratory also exhibited greater attraction to algal turf over kelp, physically moving towards this food source. In combination, the results provide evidence that A. punctulata has a feeding preference for algal turf over kelp in southern New England. Future research is warranted to further examine the grazing ecology of A. punctulata, particularly in the context of ongoing kelp forest restoration efforts in this region.
Keywords: Herbivory; Northwest Atlantic; Regime shift; Restoration; SCSU-student; dept.bio

Homogenization and miniaturization of habitat structure in temperate marine forests. - Pessarrodona, Albert; Filbee-Dexter, Karen; Alcoverro, Teresa; Boada, Jordi; Feehan, Colette; Fredriksen, Stein; Grace, Sean; Nakamura, Yohei; Narvaez, Carla; Norderhaug, Kjell; Wernberg, Thomas (Global Change Biology, 2021)
Humans are rapidly transforming the structural configuration of the planet's ecosystems, but these changes and their ecological consequences remain poorly quantified in underwater habitats. Here, we show that the loss of forest-forming seaweeds and the rise of ground-covering 'turfs' across four continents consistently resulted in the miniaturization of underwater habitat structure, with seascapes converging towards flattened habitats with smaller habitable spaces. Globally, turf seascapes occupied a smaller architectural trait space and were structurally more similar across regions than marine forests, evidencing habitat homogenization. Surprisingly, such habitat convergence occurred despite turf seascapes consisting of vastly different species richness and with different taxa providing habitat architecture, as well as across disparate drivers of marine forest decline. Turf seascapes contained high sediment loads, with the miniaturization of habitat across 100s of km in mid-Western Australia resulting in reefs retaining an additional ~242 million tons of sediment (four orders of magnitude more than the sediments delivered fluvially annually). Together, this work demonstrates that the replacement of marine forests by turfs is a generalizable phenomenon that has profound consequences for the ecology of temperate reefs., (C) 2021 John Wiley & Sons, Ltd
Keywords: Australia; Ecosystem; Forests; Humans; Miniaturization; Seaweed; Western Australia; algal turf; climate change; dept.bio; ecological impact; ecosystem; epilithic algal matrix; forest; foundation species; habitat change; habitat structure; human; kelp forest; kelp forests; miniaturization; peer-reviewed; regime shift; seaweed; sediment pollution; species richness; temperate forest